The relationship between leadership styles of nurse managers, nurse motivation, and turnover intention among nurses in Saudi Arabia: A descriptive correlational study - Aldhafeeri, Nouf Afit; Alshutwi, Sitah S.; Alotaibi, Ahoud Mofareh; Alanaza, Albandre Eid; Jaber, Amirah Hussain; Alharbi, Asrar Saleh; Alowais, Raghad Khalid (Belitung Raya Publisher - Belitung Raya Foundation, 2026)
Background: Nurses’ perceptions of their nurse managers’ leadership styles influence work motivation and turnover intention. However, limited evidence is available from Middle Eastern healthcare settings, particularly in Saudi Arabia. Objective: This study aimed to examine the relationships between nurse managers’ leadership styles, nurses’ work motivation, and turnover intention, and assessed whether work motivation moderates the association between leadership styles and turnover intention. Methods: A cross-sectional survey was conducted among 377 nurses working in governmental hospitals in Riyadh, Saudi Arabia, between January and March 2024. Leadership styles were measured across four dimensions: directive, supportive, participative, and achievement-oriented leadership. Data were analyzed using descriptive statistics, Pearson correlation analysis, and multivariate linear regression, followed by moderation analysis. Results: The mean scores for supportive, participative, directive, and achievement-oriented leadership were 5.3 ± 1.0, 5.1 ± 1.0, 5.0 ± 1.0, and 4.9 ± 1.0, respectively. The mean scores for work motivation and turnover intention were 3.5 ± 0.9 and 3.1 ± 0.8. Correlation analysis indicated that all leadership styles were positively associated with work motivation, whereas only directive leadership was negatively associated with turnover intention. In multivariable regression analyses, after adjustment for sociodemographic and professional factors, achievement-oriented leadership remained significantly associated with higher work motivation (β = 0.51, p = 0.034), while directive leadership was independently and negatively associated with lower turnover intention (β = -0.15, p = 0.022). Nationality, educational level, years of experience, and working area were also significantly associated with turnover intention in adjusted models, while educational level and years of experience were associated with nurses’ perceptions of leadership styles. Moderation analysis showed that work motivation did not significantly moderate the relationship between directive leadership and turnover intention. Conclusion: Leadership styles were significantly associated with nurses’ work motivation and turnover intention. Achievement-oriented leadership was linked to higher work motivation, while directive leadership was associated with lower turnover intention. These findings highlight the importance of strengthening nurse managers’ leadership competencies to enhance nurses’ motivation and potentially reduce turnover intentions in hospital settings.